Aspectos psicológicos do controle social - Sá, Celso Pereira de (1978)
The present work is an attempt to explore the psychologyical aspects inherent to the process of social control, according to the perspective of B. F. Skinner's 'experimental analysis of behavior'. Several current sociological propositions on some dimensions of the general issue are raised and critically articulated with the skinnerian behavioral approach. On the first chapter - 'Social Control in the Total Institutions' - a conceptual introduction to the operant conditioning is done, utilizing for this Goffman's sociological des cription of life inside those institutions. It is also discussed there some of the misinterpreations of skinnerian propositions and its mususages in closed orgunizations. On the second chapter, a comparative examination of the literary fictions '1984' and 'Walden II' is developed, with the purpose of , by focalizing their characteristical techniques of social control , raising already , in an informal way , several critical points of the issue, which come to receive a more de tailed treatment on the three following chapters. On 'Social Control in 'he Quotidian Life' it is cussed the diffuse nature the control assumes in that larger context, emphasizing the use that is make, for that end, of motivational and ideological devices. The approach to Sociology of Knowledge proposed by Berger and Luckmann is privileged in the articulation with skinnerian though. On the fourth chapter, which deals with the 'Identification of Controllers and Controllees' , it is proceeded to a beheviorist reinterpretation of the cogniivist constructs of 'intention' and 'perception', with which are usually described the control initiatives on the part of the social actors. Becker's analysis of the mechanisms of rule creation and imposition is utilized to support the strategy of reinterpretation. The final chapter explores a less traditional dimension of the issue - 'Control for Social Change'. The specific propositions from two authors - Popper and Mannheim – are here articulated with those from Skinner. Once characterized the situation of the contemporaneous society as one in incessant disordered change, the necessary conditions for a planned change and its psycho-social implications are discussed. On the conclusion of the work, it is tried to enhance the historical perspective of the social control issue, through a retrospective analysis made available by Schneider and a prospective speculation involving a social-political evaluation of the piecemeal and democratitical control of social change. It is held during that evaluation, the thesis that Skinner's behavioral engineering is piecemeal and democratic in its whole.